A study on user satisfaction towards lift facilities in Universiti Teknologi MARA (UiTM) / Nor Sulizafarahim Mohd Ali - Mohd Ali, Nor Sulizafarahim (Faculty Architecture, Planninng and Surveying, 2014)
Nowadays, many of the buildings built in the higher education institution comprise of high-rise building. This is to accommodate the growing number of students from year to year. The design of the high building must provide lift facilities as vertical transportation for users to reach the level of their own. The lift provided must be maintained property to avoid any accidents and ensure the safety of the user during use. This study is made to identify the user satisfaction toward lift facilities in UiTM. The methodology for conducting the study involved a literature review, data collection and analysis of results using the Average Index Method. The process of data collection involved obtaining primary data from the respondents by conducting questionnaire surveys at the selected building case studies, from the author’s observation and from the interview to gather more information about the maintenance management and the problem arises. From this study, it was found not all users are satisfied to the lift and it depends on the circumstances, smoothness of operation, design and maintenance of the facilities lift building.